The Features of Geo-Ecological Assessment within the Geo-Eco-Socio-Economic Approach to the Development of Northern Territories - Semyachkov, Aleksander Ivanovich; Slavikovskaya, Yuliya Olegovna (Economy of Regions, 2015)
In modern conditions, for the purpose of preservation a territory’s ecosystem at its involvement in economic circulation, it is necessary to carry out the anticipatory geo-ecological assessment for indicating the degree of resistance to hypothetical anthropogenic influence. The existing methodological approaches for performing the geo-ecological assessment are unified and can often be equally applied to various types of territories. A new methodical approach for geo-ecological assessment is brought forth in the article. It takes into account the specific character of the Ural regions northern territories. The approach is based on the point assessment of territory, which is explained by its large area, moreover, the point assessment is proposed to carry out before the development of the territory. This approach makes possible to consider the specific features of the territory’s ecosystem, namely its ability for self-restoration and self-cleaning in the process of economic development and after it. It allows carrying out the choice of economic activity direction on the whole and satisfying the condition of the minimization of the damage from violation the territory’s ecosystem and preservation its resource potential. The research results can be utilized in the studies of experts and students working on the geo-ecological assessment of territory.